PENGUKURAN PARAMETER FISIS DARI SPEKTRUM BINTANG-BINTANG B-EMISI - Shania Bernadi, Ancilla
B-emission star is star in spectrum class B whose spectrum have had or has emission lines in its spectra, especially in H? line region. Be star has many variabilities in its spectra. This final project aims to examine the physical parameters of the spectrum of B-emission stars. The stellar objects selected to observed are based on consideration of the variations in the spectrum of their stars. In the end, 6 stars were selected, namely EW Lac (HR 8731), 48Lib (HR 5941), V923 Aql (HR 7415), 51 Oph (HR 6519), V1339 Aql (HR7554), Del Cen (HR 4621). All of these stars have significant variations in V/R or different forms of the spectrum. There are several results obtained from data processing and discussion. The first, the six of Be stars were selected, the four of which can be analyzed for their V/R values because they have a double peak and shell spectrum profile. Several patterns of V/R variation were successfully obtained, one of which is the HR 5941 star which has an upward trend but the period has not yet been seen. Based on the reference, the V/R variability period of the star 5941 is 17 years, while the data we have is the last 10 years only. Meanwhile, the HR 7415 star shows a recurring period that occurs every 6-7 years. The second, the E/C variability value can be analyzed for the six stellar objects because of to get the E/C value only requires the emission peak intensity and the continuum line. Most of the E/C values of the stars are fairly constant. Subsequently, the radius of the star can be found using the separation of the two emission peaks for a star with both a double peak and a shell. There are no special patterns found in the observed stars, but changes can still be observed. In the star HR 9731, the value of the star's radius doubled to 9 times and then decreased to only about 2. If v sin i gets bigger, which means that the absorption profile is getting deeper, then the value of the radius will be greater. The radius of a star with a shell profile is higher than with a double peak type star. Some relation regarding Be stars parameter can be found here. One of them is the proportional relation between FWHM and W in almost all objects, but these two parameters has no correlation. Proportional relation also can be found between FWHM and disk radii. Furthermore, the other relation can’t be found because Be stars is a unique object individually so that it is difficult to find a general relation for all Be stars.